Factors affecting the feeding value of sorghum silage - Smith, E.F.; Richardson, D.; Fairbanks, G.E.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This is the third year of an experiment designed to investigate factors that affect the feeding value of sorghum silage. Data reported in Circular 383, 1960-61, indicated that almost without exception, average daily gain, silage dry matter consumption, and silage dry matter percent were positively correlated. Pounds of silage dry matter required to produce a pound of gain were negatively correlated with average daily gain, silage dry matter and daily dry matter consumption. Winter gains also ranked in the same order as the percentage of grain in the silage, i.e., the higher the grain content, the greater the gain. However, digestion coefficients, using steer calves, were lower with the high-grain silage, suggesting the possibility of appreciable nutrient loss in undigested grain.
Keywords: Sorghum silage; Feeding value; Beef; Gain